TAAT technology toolkits and their strategic delopyment: Clearinghouse technical report series 001 - Technologies for African Agricultural Transformation (Technologies for African Agricultural Transformation, 2018)
The African Development Bank recently launched Feed Africa: A Strategy for Agricultural Transformation in Africa. This loan program is intended to unlock Africa’s agricultural potential and boost job creation with a view to diversifying African economies and to better meet the Sustainable Development Goals related to poverty reduction and ending hunger and malnutrition. Technologies for African Agricultural Transformation (TAAT) is a flagship program within the Feed Africa Strategy aimed at modernizing African agriculture through the advancement of agricultural technology in a way that improves the business of agriculture across Africa, thus raising agricultural productivity, mitigating risks, and promoting sustainable enterprise diversification. To achieve these goals, TAAT focuses upon the identification, promotion and dissemination of proven technologies and management innovations. It is led by the International Institute of Tropical Agriculture (IITA) and structured as a series of Value Chain Compacts, each with its own Technology Toolkits, impact targets, and partnership arrangements.